2017
DOI: 10.1002/jmri.25865
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory motor dysfunction in parkinson's disease subtypes

Abstract: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:1610-1615.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…We find a consistent significant correlation between MDS-UPDRS scores and GABA levels in the motor cortex, both ON (Panel c) and OFF medication (Panel d), but no significant correlations for the thalamus (Panels a and b) and visual cortex (Panels e and f). GABA, gamma-aminobutyric acid; MDS-UPDRS, Movement Disorders Society Unified Parkinson's Disease Rating Scale; tCre, total creatine from those by Dharmadhikari et al, who showed increased GABA levels in the thalamus of Parkinson's disease patients (Dharmadhikari et al, 2015), or those by Gong et al, who found a reduction of GABA levels in patients in a larger thalamus/basal ganglia voxel (Gong et al, 2017). We considered several possible explanations for this null finding.…”
Section: Parkinson's Disease Is Not Associated With Increased Thalamentioning
confidence: 89%
See 4 more Smart Citations
“…We find a consistent significant correlation between MDS-UPDRS scores and GABA levels in the motor cortex, both ON (Panel c) and OFF medication (Panel d), but no significant correlations for the thalamus (Panels a and b) and visual cortex (Panels e and f). GABA, gamma-aminobutyric acid; MDS-UPDRS, Movement Disorders Society Unified Parkinson's Disease Rating Scale; tCre, total creatine from those by Dharmadhikari et al, who showed increased GABA levels in the thalamus of Parkinson's disease patients (Dharmadhikari et al, 2015), or those by Gong et al, who found a reduction of GABA levels in patients in a larger thalamus/basal ganglia voxel (Gong et al, 2017). We considered several possible explanations for this null finding.…”
Section: Parkinson's Disease Is Not Associated With Increased Thalamentioning
confidence: 89%
“…previous studies used a GABA-to-water ratio, whereas here we used a GABA-to-creatine ratio. There is some evidence that in Parkinson's disease, creatine (and NAA) is also reduced in the thalamus and basal ganglia (Gong et al, 2017;Kickler et al, 2007). However, reduced creatine levels in Parkinson's disease would bias us toward confirming, rather than rejecting, our a priori hypothesis of an increased thalamic GABA-to-creatine ratio in Parkinson's disease.…”
Section: Parkinson's Disease Is Not Associated With Increased Thalamentioning
confidence: 89%
See 3 more Smart Citations